Targeted Suppression of Salmonella enterica Serotype Enteritidis via siRNA-Functionalized Graphene Oxide Nanocarriers Against 16S rRNA Gene (Development Engineering Conferences Center Articles Database, 2025)
Antimicrobial resistance in Salmonella enterica serotype Enteritidis demands new, gene-targeted therapeutics. We engineered a graphene oxide (GO) nanocarrier to deliver small interfering RNA (siRNA) directed against the essential 16S rRNA gene and evaluated its antibacterial efficacy in vitro. GO was synthesized via a modified Hummers’ method, activated with EDC/NHS, and covalently conjugated to anti-16S siRNA; physicochemical features were verified by UV–Vis spectroscopy (π–π* ≈230 nm; n–π* ≈300 nm). Efficient bacterial uptake GO–siRNA was confirmed by fluorescence microscopy. Functional activity was quantified by colony-forming unit (CFU) assays and RT-qPCR. Relative to untreated, GO-only, and siRNA-only controls, GO–siRNA reduced viable CFUs by >70% after 24 h (one-way ANOVA with Tukey’s post hoc, p